Dermoscopy of small melanomas: just miniaturized dermoscopy?. (11th June 2014) - Seidenari, S.; Ferrari, C.; Borsari, S.; Fabiano, A.; Bassoli, S.; Giusti, F.; Ponti, G.; Magnoni, C.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Only sporadic reports on the dermoscopic aspects of small melanomas are available at present. As small melanomas are those in an initial growth phase, it is important to know whether they have peculiar dermoscopic features enabling early diagnosis. What does this study add? To the best of our knowledge, this article presents the largest dermoscopic database on small melanomas and micromelanomas.